Implementasi dan Akibat Hukum Penerapan Asas Lex Spesialis Derogat Legi Generalis terhadap Keistimewaan Aceh - Titis Anindyajati; Winda Wijayanti; Intan Permata Putri (The Constitutional Court of the Republic of Indonesia, 2021)
The contestation to National Election Act’s implementation or principle of lex specialis derogat legi generalis as rule’s problem reference to regional dispute in Aceh. This research is a normative legal related to Aceh Election and Qanun on Election. The crucial problem with existence of special rules of Aceh’s privilege are not set by threshold conditions. Lex specialis derogate legi generali’s principle cannot be used in election dispute will contradict the 1945 Constitution. The Election Act cannot be ruled as dispute basis to Constitutional Court. The principle can be applied to cases that requirements, so harmonious legal drafting becomes urgency to formalize a special judicial body.